To find the measure of angle \( \angle JHI \), we can use the fact that the sum of adjacent angles that form a straight line (or are on a straight angle) equals 180°.
We know:
- \( \angle GHI = 135° \)
- \( \angle GHJ = 112° \)
To find \( \angle JHI \), we can use the relationship:
\[ \angle GHI = \angle GHJ + \angle JHI \]
Substituting the known values:
\[ 135° = 112° + \angle JHI \]
Now, subtract \( 112° \) from both sides:
\[ \angle JHI = 135° - 112° = 23° \]
Thus, the measure of \( \angle JHI \) is \( 23° \).
The correct response is:
23°